Structure and Stability of Duplex DNA Containing (5’S)-5’,8-Cyclo-2’-Deoxyadenosine: An Oxidatively-generated Lesion Repaired by NER - Zaliznyak, Tatiana (2012)
Cellular respiration and ionizing radiation generate 5’,8-cyclo-2’-deoxyribonucleosides, an especial type of DNA damage that involves two modifications in the same nucleotide. These lesions evade the action of base excision glycosylases and their removal is a function of the nucleotide excision repair pathway. Diastereomeric 5’,8-cyclo-2’-deoxyadenosine block mammalian DNA replication, diminish the levels of DNA transcription and induce transcriptional mutagenesis. Using solution state NMR spectroscopy and restrained molecular dynamics simulations, we have determined the structure of an undecameric DNA duplex having a centrally located (5’S)-5’,8-cyclo-2’-deoxyadenosine residue paired to T. The damaged duplex structure is a right-handed helix having Watson-Crick base-pair alignments throughout and 2-deoxyribose puckers within the B-form conformation. Only small structural perturbations are observed at the lesion-containing and 5’-flanking base-pair. The 2-deoxyribose of the damaged nucleotide adopts the O4’-exo conformation and the S-cdA•T base-pair is propeller twisted. The 5’-lesion-flanking base is tilted forming a significantly buckled base-pair with its partner guanine. Analysis of UV-melting curves indicates mild thermal and thermodynamic destabilization on the damaged duplex. The S-cdA•T duplex structure shows many similarities and some intriguing differences with the recently reported structure of an S-cdG•dC duplex(31) that suggest different lesion site dynamics.